CIVILIZATION PHENOMENON OF CHINA - Михайлов, В. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article tells about the birth and genesis of Chinese-Far-Eastern civilization. It gives an analysis of social-philosophical and social-economic reasons of civilized progress of China.